Pemberdayaan Karang Taruna Dusun Ujung Gersik Melalui Kegiatan Positif Dan Optimalisasi Sumber Daya Alam Di Dusun Ujung Gersik - Ilmi, Nurul; Sufi, Muhammad; Sari, Kartika (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Empowering the Ujung Gersik Hamlet Youth Organization is a challenge for students. The head of Ujung Gersik Hamlet asked KKN students to activate the youth organization and solve the problems that occur among the youth there. The younger generation is involved in the world of juvenile delinquency such as drinking alcohol. This condition is a challenge in itself for students who carry out real work courses (KKN), so implementing the empowerment of the younger generation requires extra effort and approach. The method of service through this KKN program is to invite the youth of Ujung Gersik Hamlet to join the youth organization and invite them to be actively involved in positive activities that have been prepared in the KKN work program with village officials and youth organization administrators. Pemberdayaan karang taruna Dusun Ujung Gersik merupakan tantangan bagi mahasiswa. Kepala Dusun Ujung Gersik meminta mahasiswa KKN untuk mengaktifkan organisasi karang taruna dan menyelesaikan permasalahan yang terjadi pada pemuda di sana. Para generasi muda terlibat dalam dunia kenakalan remaja seperti meminum minuman keras. Kondisi ini menjadi tantangan tersendiri bagi mahasiswa yang melaksanakan kuliah kerja nyata (KKN), sehingga pelaksanaan pemberdayaan generasi muda membutuhkan usaha dan pendekatan yang ekstra. Metode pengabdian melalui program KKN ini adalah mengajak para pemuda Dusun Ujung Gersik untuk bergabung ke dalam organisasi karang taruna dan mengajak mereka untuk terlibat aktif dalam kegiatan-kegiatan positif yang telah disusun dalam program kerja KKN bersama para perangkat desa dan pengurus karang taruna.